2023
DOI: 10.21203/rs.3.rs-2742573/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine Learning Algorithms for a Novel Cuproptosis-related Gene Signature of Diagnostic and Immune Infiltration in Endometriosis

Abstract: Endometriosis (EMT) is a chronic hormone-dependent disease where in viable endometrial tissue is transplanted outside the uterus. Interestingly, immune infiltration is significantly involved in EMT pathogenesis. Currently, no studies have shown the involvement of cuproptosis-related genes (CRGs) in regulating immune infiltration in EMT. This study identified three CRGs such as GLS, NFE2L2, and PDHA1, associated with EMT using machine learning algorithms. These three CRGs were upregulated in the endometrium of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…ML models showed a high classification performance and were able to consistently reveal a number of pollutants associated with the disease. Genetic studies analyzing the expression of long non-coding RNAs [104] and of genes [105,106] reported an up-regulation of the genes involved in vasculogenesis, cell proliferation, cell-matrix adhesion, cell differentiation, extra-cellular matrix, remodeling muscle contraction, apoptosis, immune response and chemotaxis.…”
Section: Applications Of Ai To Endometriosis and Adenomyosis Researchmentioning
confidence: 99%
“…ML models showed a high classification performance and were able to consistently reveal a number of pollutants associated with the disease. Genetic studies analyzing the expression of long non-coding RNAs [104] and of genes [105,106] reported an up-regulation of the genes involved in vasculogenesis, cell proliferation, cell-matrix adhesion, cell differentiation, extra-cellular matrix, remodeling muscle contraction, apoptosis, immune response and chemotaxis.…”
Section: Applications Of Ai To Endometriosis and Adenomyosis Researchmentioning
confidence: 99%